Inscriptions in the private sphere in the Greco-Roman world - Benefiel, Rebecca 1975-; Keegan, Peter (Lecturer in Roman history) (Brill Studies in Greek and Roman Epigraphy, 2016)
When one thinks of inscriptions produced under the Roman Empire, public inscribed monuments are likely to come to mind. Hundreds of thousands of such inscriptions are known from across the breadth of the Roman Empire, preserved because they were created of durable material or were reused in subsequent building. This volume looks at another aspect of epigraphic creation - from handwritten messages scratched on wall-plaster to domestic sculptures labeled with texts to displays of official patronage posted in homes: a range of inscriptions appear within the private sphere in the Greco-Roman world. Rarely scrutinized as a discrete epigraphic phenomenon, the incised texts studied in this volume reveal that writing in private spaces was very much a part of the epigraphic culture of the Roman Empire.